The effectiveness of service quality performed by The New Straits Times Press (Malaysia) Berhad towards customer satisfaction / Asmahani Aminudin - Aminudin, Asmahani (Faculty of Business and Management, 2007)
Customer nowadays rates service quality as the thing that they seek in most service industry. The service quality later leads to high customer satisfaction. Customer satisfaction is crucial to the survival of any business organization. However, service failures are often unavoidable due to human and non-human errors. Such failures to perform a service inevitably lead to customer dissatisfaction. This study is mainly focuses on the effectiveness of service quality performed by The New Straits Times Press (Malaysia) Berhad towards customer satisfaction. First objective is to examine whether current service given by NSTP meets customer perception and expectation. Customer will satisfy if perceived service is greater than expected service. Second objective is to determine the relationship between service quality and customer satisfaction. The relationship examined by using Pearson Correlation. Third objective is to identify a good solution on how to deliver best service to customer, Some recommendations have been suggest as the solution. The researcher chooses descriptive as the research design. Simple random sampling (probability technique) is used because the element in the population has a known and equal probability of selection. Every element is selected independently of every elements and the sample is drawn by a random procedure. The study was carried out at The New Straits Times Press (Malaysia) Berhad, Kuala Lumpur. Beside that, some suggestions have been recommending to The New Straits Times Press (Malaysia) Berhad so that can help to improve the service quality in future.